2010
DOI: 10.1152/ajpheart.00667.2009
|View full text |Cite
|
Sign up to set email alerts
|

Preoxygenated hemoglobin-based oxygen carrier HBOC-201 annihilates myocardial ischemia during brief coronary artery occlusion in pigs

Abstract: Because of their ability to perfuse remote regions and deliver oxygen, hemoglobin-based oxygen carriers (HBOCs) may be considered in the treatment of several ischemic conditions such as acute coronary syndromes or high-risk percutaneous intervention. Here we studied the effects of intracoronary infusion of ex vivo preoxygenated HBOC-201 during brief total coronary artery occlusion (CAOs) on myocardial oxygenation and left ventricular (LV) function in a large animal model and investigated the influence of HBOC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Hemoglobin-based oxygen carriers (HBOCs) are red blood cell substitutes under development for more than three decades [ 3 ]. Our previous work and other studies indicated that HBOCs are promising candidates to prevent many organs from I/R injury [ 4 7 ]. Functionally, they allow delivery of more oxygen (O 2 ) to hypoxic tissues due to their higher O 2 affinity, lower viscosity, and smaller mean diameter than human erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin-based oxygen carriers (HBOCs) are red blood cell substitutes under development for more than three decades [ 3 ]. Our previous work and other studies indicated that HBOCs are promising candidates to prevent many organs from I/R injury [ 4 7 ]. Functionally, they allow delivery of more oxygen (O 2 ) to hypoxic tissues due to their higher O 2 affinity, lower viscosity, and smaller mean diameter than human erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…One study has demonstrated that intracoronary infusion of preoxygenated HBOC-201 preserved myocardial metabolism, regional oxygen delivery and left ventricular function produced by a three minute coronary artery occlusion. 36 Importantly, intracoronary infusion of nonoxygenated HBOC-201, Ringers solution or no treatment resulted in immediate loss of ventricular function in the ischemic region and evidence for anaerobic metabolism. 36 These findings have important clinical implications regarding the potential benefits of HBOC-201 as an organ preservation fluid and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…), anesthetized with pentobarbital (15 mg/kg i.v. ), intubated and mechanically ventilated with O 2 and N 2 (1:3 v/v), and instrumented as previously described [ 26 , 44 ]. Catheters were placed in the external jugular vein for maintenance of anesthesia (pentobarbital, 10–15 mg/kg/h) and infusion of physiological saline, and the left femoral artery for measurement of arterial blood pressure.…”
Section: Methodsmentioning
confidence: 99%